International students creating comedy to foster wellbeing and connectedness: ‘Are you joking?’ - de saint Léger, Diane; Lysk, Jayne; Sallis, Richard; McConville, Kelly; Clayman, Danielle (Journal of International Students, 2024)
It is well established that international students attending higher education institutions in Australia and other parts of the world face challenges that can affect their state of well-being and connectedness. Higher education institutions have attempted to counter these issues by providing specifically designed programs with varying success. This study builds on some of the more successful programs that draw on the relationship between creativity and collaboration. The program aimed to foster international students’ well-being by teaching them how to harness their creative potential and explore through stand-up comedy the funny side of life as international student in Australia. The analysis shows that the program positively enhanced well-being by fostering a sense of connectedness and by providing a space to take risks in a safe and supportive fashion. Data also indicated that the program contributed to the development of knowledge and skills transferrable to other academic and non-academic contexts.